Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Targeting EFEMP1 enhances chondrogenesis and inhibits hypertrophic differentiation in a spontaneous osteoarthritis mouse model - Yuhan Chang; Pei-Heng Jiang; Yung-Heng Hsu; Yu-Chih Lin; Chih-Chien Hu; Yi-Zhen Li; Steve Wen-Neng Ueng; Mei-Feng Chen (Journal of Molecular Medicine, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Ultrasensitive and rapid detection of botulinum neurotoxin serotype A via Argonaute-mediated signal cascade with a pregnancy test strip readout - Weiling Yu; Yukang Chen; Shujie Zhang; Ruina Zheng; Zhanyin Lin; Yujun Mei; Qiancheng Zhan; Bowen Xue; Jinxuan Fan; Bo Liu; Song Gao; Yuan-Di Zhao; et al. (Food Chemistry, 2026)

Biogeochemical cycling and fate of PAHs in coral reef ecosystem: Associations with coral holobiont microbial functional profiles - Mei Xiong; Minwei Han; Kefu Yu; Xuejiao Lin; Xiangrong Xu (Water Research, 2026)

Tailored Cu active sites in 2D MOF-derived carbon nanosheets for dual electrochemical detection of chloramphenicol and paracetamol - Zhi-Lun Wu; Tsai-Ting Liu; Mei-Hong Tang; Sheng-Fei Lin; Yu-Jen Shih (Chemical Engineering Journal, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

Multi-omics Analysis Reveals the Protection of a Quadruple Probiotic Mixture in Experimental Autoimmune Hepatitis - Yu Chen; Shuhui Wang; Anzhuo Chen; Zhuoying Lin; Han Wang; Wanneng Li; Jun Liu; Jia Yao; Dean Tian; Yu Lei; Mei Liu (Probiotics and Antimicrobial Proteins, 2026)

Integrated multi-matrix bile acid metabolic metrics (BAMMs): A methodological framework for functional metabolic phenotyping in human subjects - Cheng-Hung Yang; Hsiang-Yu Tang; Chun-Ming Fan; Jui-Fen Lin; Mei-Ling Cheng (Analytica Chimica Acta, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Corrigendum to “OsCOPT7 is involved in copper accumulation and transport through xylem” [J Hazard Mater 477 (2024) 135245] - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Sulfur-doped MgFe2O4 with oxygen vacancies: Unveiling the synergistic role of electron transfer pathways in boosting radical generation for efficient peroxymonosulfate activation - Lin Wang; Shoudie Yue; Mengyang Li; Mei Wang; Wenqi Wang; Jirong Yu; Shaolong Wang; Baojun Liu (Chemical Engineering Journal, 2026)

A Non-spinal Neural Circuit for Transmitting Information of Bladder Conditions - Zhenxiang Zhu; Zhuang Liu; Zan Wang; Guangfu Cui; Mei-Yu Shi; Kunzhang Lin; Yuxiang Qiu; Tengxiao Si; Peng Chen; Qing Liu; Guo-Qiang Bi; Jie Wang; et al. (Neuroscience Bulletin, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

Towards integrated pollution control in inland watersheds: addressing multiple challenges through watershed-scale technological systems and targeted control strategies - Mei-Yun Lu; Jie Ding; Xin-Lei Yu; Zi-Tong Zhao; Yi-Lin Zhao; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Environmental Pollution, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Building a yeast cell factory for green biomanufacturing of (R)-(+)-γ-decalactone: A natural peach-like aroma compound - Yizi Yu; Kaifeng Wang; Tao Sun; Shushu Li; Ying Zhou; Mei-Li Sun; Lu Lin; Rodrigo Ledesma-Amaro; Xiao-Jun Ji (Chemical Engineering Journal, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Ultrafine particles and stroke hospitalizations: New insights of exposure-outcome threshold, daily peaks, and comorbidities - Liqiong Guo; Wendy Weller; Christopher Thorncroft; Fangqun Yu; Najm Alsadat Madani; Yukang Xue; Mei Zhao; Shao Lin (Journal of Hazardous Materials, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Alpha-ketoglutarate restores oral epithelial homeostasis via FOXM1-mediated cell cycle regulation - Yuan Wang; Yimeng Cai; Qi Yin; Shuqin Cao; Yuyu Li; Yuhan Li; Qiwen Li; Qian Wang; Pochun Lin; Li Mei; Malcolm Xing; Leixiao Yu; et al. (Science China Life Sciences, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

A machine learning and box modeling approach to comparing the atmospheric chemistry of high- and low-ozone and PM₂.₅ episodes - Ahsan Mozaffar; Yan-Lin Zhang; Yihang Hong; Mei-Yi Fan; Yu-Chi Lin (Atmospheric Research, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

CT-HiffNet: A contour-texture hierarchical feature fusion network for cropland field parcel extraction from high-resolution remote sensing images - Hao Wu; Junyang Xie; Weihao Deng; Anqi Lin; Abdul Rashid Mohamed Shariff; Shamshodbek Akmalov; Wenbin Wu; Zhaoliang Li; Qiangyi Yu; Qunming Wang; Jian Zhang; Xin Mei; et al. (Computers and Electronics in Agriculture, 2025)

A unified framework for predicting vertical bearing capacity of fully embedded pipes/tunnels in clay seabed based on the undrained failure mechanisms - Yu Zhao; Xing-Tao Lin; Wei-Jian Li; Jun-Chen Zhang; Zhi-Yao Tian; Quan-Mei Gong (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A systematic review of concrete self-healing mechanism and analysis of new research directions - Quan Xue; Xianlei Feng; Yumeng Sun; Zheng Si; Liwei Zhang; Zhenhua Zhou; Yu Zhong; Kaiyuan Mei; Guanghua Lin; Huiyizhe Zhao (Journal of Environmental Chemical Engineering, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Improving stability and UV protection properties of phycocyanin nanoparticle-based Pickering emulgels via amorphous cationic starch complexation - Yacheng Hao; Jiahao Mei; Dongfang Ling; Zhe Zhang; Sai Li; Zhiyong Gong; Xin Liu; Mingfeng Xu; Yilin Lin; Rongrong Yu (Carbohydrate Polymers, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Inverse Admittance Characteristics of Gastric Cancer Cells Measured by a Validated Dielectrophoretic Microfluidic Platform - Jia‑Jiun Tsai; Yun-Jung Tsai; Mei Yu Huang; Chun-Ping Jen; Shu-Hui Lin (Journal of Medical and Biological Engineering, 2025)

Correction: Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Analytical and usability comparison of microsampling dried blood spot devices for glucocorticoid detection in sports using ultra-high-performance liquid chromatography–tandem mass spectrometry - Cheng-Chia Chen; Yu-En Lin; Mei-Chich Hsu; Yu-Chuan Lin; William Chih-Wei Chang (Analytica Chimica Acta, 2025)

Distinct cellular localization of α- synuclein and β-synuclein in the chick retina - Fang He; Lin Liu; Shaoxuan Wang; Xin Lin; Guiyu Guan; Xiaoqian Lai; Xi Yu; Xiaotian Wu; Zhihao Shen; Bilin Rao; Mei-Ling Gao; Xuejiao Chen; et al. (Brain Structure and Function, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Complex of butyric acid with the amorphous region of starch granules via high-pressure processing - Amy Hui-Mei Lin; Shaun Yong Jie Sim; Choy Eng Nge; Ting-Jang Lu; Nur Syahirah Amirruddin; Amanda Xin Yi Sng; Kai Ting Wong; Yoganathan Kanagasundaram; Andrea Gómez-Maqueo; Hui Yu Sim (Food Chemistry, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Fermented Soybean Pulp Alleviates Disease Progression of 5×FAD Model Mice - Chun-Yen Yang; Yu-Hsuan Liu; Ta-Chun Lin; Kuo-Hsuan Chang; Hsiu Mei Hsieh-Li (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder of the central nervous system, characterized by memory loss and cognitive decline. The two main hypotheses regarding AD involve the accumulation of amyloid-β (Aβ) forming plaques and the intracellular hyperphosphorylation of tau protein, leading to the formation of neurofibrillary tangles (NFT). These processes are accompanied by neuroinflammation and oxidative stress, and eventual neuronal death. While soy foods are widely recognized for their nutritional benefits, soybean pulp (okara), the residue left over from making tofu or soybean milk, is mostly discarded as kitchen waste, despite being rich in nutrients such as dietary fiber, protein, and isoflavones. This underutilized byproduct may serve as a valuable resource for functional food development and sustainable resource use. In this study, fermented soybean pulp (FS) demonstrated neuroprotective effects. In vitro, FS at concentrations of 0.001 µg/mL and 0.01 µg/mL significantly improved cell viability in Aβ-induced HT-22 cells and reduced lipid peroxidation. Further, in vivo oral administration of FS attenuated the cognitive deficits of 5 × FAD mice, enhancing both short and long-term memory and reducing anxiety-like behaviors. Immunohistochemical analysis revealed that the FS-treated 5 × FAD mice group significantly reduced hippocampal amyloid plaque accumulation and gliosis. FS also upregulated the expression levels of brain-derived neurotrophic factor (BDNF), PSD95, and synaptophysin, while preventing hippocampal neuronal loss. Mechanistically, FS may activate the Nrf2 antioxidant pathway and NF-κB-mediated inflammation through the modulation of the Akt/GSK3β signaling axis in the hippocampus. These molecular actions likely contribute to increased antioxidant enzymes and suppressed neuroinflammatory responses. Overall, this study suggests that FS has therapeutic potential for alleviating cognitive and behavioral impairments in AD. Moreover, the repurposing of soybean pulp, which would otherwise be discarded, enhances its utilization value and supports sustainable green recycling.

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Binding of Chinese quince oligomeric proanthocyanidins with different structures to sarcoplasmic and myofibrillar protein in chicken: Role of conformational changes and heterocyclic amine inhibition - Mei-Qi Yang; Hao Liu; Yi-Lin Chen; Jia-Hao Wang; Lin Xiao; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma (Food Chemistry, 2025)

A GTPase activating protein Polrg1 regulates the development and cellulase expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Lin Xu; Ziyin Xu; Yihang Qu; Yu Wang; Chunna Sun; Mei Chen; Zhonghai Li (World Journal of Microbiology and Biotechnology, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Elucidating CTLA-4’s role in tumor immunity: a comprehensive overview of targeted antibody therapies and clinical developments - Juan Fu; Lin Mao; Yu Jiao; Desheng Mei; Yadong Chen (Molecular Diversity, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Ontology-driven knowledge graph for decision-making in resilience enhancement of underground structures: Framework and application - Bin-Lin Gan; Dong-Mei Zhang; Zhong-Kai Huang; Fei-Yu Zheng; Rui Zhu; Wei Zhang (Tunnelling and Underground Space Technology, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A Rho-Type GTPase Protein Pocdc42 Regulates the Development and Cellulase Expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Ziyin Xu; Lin Xu; Yu Wang; Yihang Qu; Chunna Sun; Mei Chen; Zhonghai Li (Current Microbiology, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

An autocorrelation-based residual-stacking approach for GNSS multipath and diffraction mitigation and its application in high mountainous areas - Yumiao Tian; Wenhao Xiong; Yibing Liang; Yu Tang; Xi Mei; Xuefeng Yang; Miao Lin (Journal of Geodesy, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Functional characterization of chemosensory proteins in three sympatric Tomicus bark beetles feeding on Pinus yunnanensis: Implication for the conservation and divergence of ligand-binding profiles - Lin-Mei Pu; Peng-Fei Wang; Yu-Yue Lu; An-Jin Yang; Li-Li Liu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Research on ship dynamic feature extraction and prediction method based on visual data - Siling Lin; Yong Li; Yu Hu; Jia Shi; Shaohua Wang; Peng Wang; Qiang Mei; Xiao Li; Haowen Wei (Ocean Engineering, 2025)

Parallel floral evolution of Lilium species pollinated by pierid butterflies - Yun-Bo Duan; Hong-Qiang Lin; Zhe Chen; Chang-Qiu Liu; Yu-Mei Yuan; Yun-Dong Gao; Mei-Yan Lei; Mao-Lin Wang (Flora, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Transcriptional mechanisms underlying thiazolidine-4-carboxylic acid (T4C)-primed salt tolerance in Arabidopsis - Wei-Yung Hsu; Yi-Zhen Wu; Yu-Min Lin; Mei-Juan Zheng; Liang-Jwu Chen; Chuan-Ming Yeh (Plant Cell Reports, 2025)

Slow-release ferrous effects on synchronous stabilization of lead, cadmium, and arsenic in soil - Zhi Jiang; HongZhen Ran; Lin Yu; Mei Jiang; Weichun Yang (Environmental Geochemistry and Health, 2025)

Unearthing Vertical Stratified Archaeal Community and Associated Methane Metabolism in Thermokarst Sediments - Ze Ren; Mei Wang; Jinlei Yu; Lixiang Zhang; Zhenmei Lin; Xia Li; Yunlin Zhang (Environmental Microbiology, 2025)
Thermokarst lakes are hotspots for greenhouse gas emissions across the Arctic and Qinghai‐Tibet Plateau. Investigating the vertical stratification of archaeal communities in thermokarst lake sediments is essential for understanding their ecological roles and contributions to methane production. Here, we analysed archaeal communities along a depth gradient in thermokarst lake sediments. Alpha diversity (richness and Shannon index) generally decreased with depth. Euryarchaeota was the most abundant phylum, though its relative abundance declined with depth, while Thaumarchaeota increased. At the order level, Methanosarcinales and Nitrosopumilales showed increased relative abundance with depth, indicating adaptation to deeper anoxic layers, whereas Methanomicrobiales and Methanotrichales decreased. Beta diversity increased with depth, shifting from stochastic to deterministic processes. Network topology revealed reduced species connectivity but heightened modularity at depth, signalling niche specialisation. Functionally, genes associated with the initial steps of methane metabolism ( Fwd , Mtd , Mer ) increased with depth, while those involved in later steps ( Mtr , Mcr ) decreased, suggesting reduced energy conservation efficiency and lower overall methanogenesis rates in deeper sediments. These findings highlight the significant impact of vertical stratification on archaeal community structure, interaction networks, and functional capabilities.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Microplastics enhance laccase-driven bisphenol A removal in multipollutant wastewater - Jie Zhang; Jiongna Liu; Xinyi Liu; Yu Su; Chunyang Yu; Xuemei Tan; Lin Zhuo; Mei Ye; Qinglin Luo; Biao Li (Journal of Environmental Management, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Boosted catalytic soot oxidation by hierarchical hollow cobalt oxide constructed from a Template-Sacrificial Method: Promoting Roles of morphologies and oxygen vacancies - Yu-Chih Tsai; Mei-Chen Wan; Shen Yan Lin; Vo Thi Thanh Thuy; Nguyen Nhat Huy; Duong Dinh Tuan; Jechan Lee; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Transformation fate of bisphenol A in aerobic denitrifying cultures and its coercive mechanism on the nitrogen transformation pathway - Pei Hong; Yu Pang; Jing Xu; Qi Wang; Huiju Lin; Yuefei Ruan; Yilin Shu; Kai Zhang; Kenneth Mei Yee Leung (Environmental Research, 2025)

Accumulation of microplastics in various organs of fiddler crabs and sea cucumbers across the coastal habitats in Singapore - Jenny Fong; Ashwini Suresh Kumar; Zhen Yu Choy; Yi Hong Tan; Jasmine Anya Putri Gowidjaja; Mei Lin Neo (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Monitoring soil arsenic content in densely vegetated agricultural areas using UAV hyperspectral, satellite multispectral and SAR data - Yanan Zhou; Chang Liu; Jie Wang; Mei-Wei Zhang; Xiaoqing Wang; Ling-Tao Zeng; Yu-Pei Cui; Huili Wang; Xiao-Lin Sun (Journal of Hazardous Materials, 2025)

Biotic plant-soil feedbacks alone do not explain why more diverse plant communities are less invasible - Hao-Ming Yuan; Xiao-Mei Zhang; Peter Alpert; Lin-Xuan He; Wei Xue; Lin Huang; Ling Peng; Fei-Hai Yu (Plant and Soil, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Long-term alterations of nutrient dynamics and phytoplankton communities in Daya Bay, South China Sea - Ranjan Pradeep Rajapaksha; Mei-Lin Wu; Yu-Tu Wang; Gayan Bandara; Keerthi Sri Senarathna Atapaththu; You-Shao Wang (Marine Pollution Bulletin, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

Important contributions of natural gas combustion to atmospheric nitrate aerosols in China: Insights from stable nitrogen isotopes - Yu-Chi Lin; Mei-Yi Fan; Yihang Hong; Mingyuan Yu; Fang Cao; Yan-Lin Zhang (Science Bulletin, 2024)

Identifying heavy metal sources and health risks in soil-vegetable systems of fragmented vegetable fields based on machine learning, positive matrix factorization model and Monte Carlo simulation - Jiacheng Shi; Yu Yang; Zhijie Shen; Yuding Lin; Nan Mei; Chengzhong Luo; Yongmin Wang; Cheng Zhang; Dingyong Wang (Journal of Hazardous Materials, 2024)

Migration mechanism of atrazine in the simulated lake icing process at different freezing temperatures based on density function theory - Yan Zhang; Hao Lin; Aixin Yu; Xiaozhuang Wang; Yucan Liu; Tongshuai Liu; Chen Zhao; Rui Mei (Journal of Environmental Sciences, 2024)

A novel vanadium-copper rechargeable battery for solar energy conversion and storage - Chunkun Lin; Jiangxin Wang; Kaixin Zhang; Huibin Shi; Yibing Liu; Kuanhong Mei; Minmin Liu; Yu Zhang; Shuo Li (Chemical Engineering Journal, 2024)

Conjugated microporous polymer derived hierarchically porous N-rich nanocarbon as a durable electrocatalyst for oxygen reduction reaction in Zn-air battery - Lunjie Liu; Zian Xu; Yu Xia; Mei-Yan Gao; Qin Jin; Baobing Zheng; Chongxuan Liu; Shaoqing Chen; Zhe Zhang; Hsing-Lin Wang (Chemical Engineering Journal, 2024)

Self-Healing fluorinated polymer deep eutectic electrolytes for stable lithium metal batteries - Yingzhi Yu; Canhui Ling; Jixu Yang; Antai Zhu; Tuoya Naren; Yuxin Chen; Yuejiao Chen; Weifeng Wei; Xiaobo Ji; Chengchao Li; Libao Chen; Lin Mei; et al. (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

OsCOPT7 is involved in copper accumulation and transport through xylem - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2024)

Anaerobic oxidation of methane and greigite formation: Evidence of isotopically heavy pyrite in Pleistocene coastal sediments from the South Yellow Sea - Xiaoxiao Yu; Xi Mei; Jianxing Liu; Baichuan Duan; Rui Zhang; Tiegang Li; Gangjian Wei; Mang Lin (Global and Planetary Change, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Underwater Image Enhancement Based on Light Field-Guided Rendering Network - Chia-Hung Yeh; Yu-Wei Lai; Yu-Yang Lin; Mei-Juan Chen; Chua-Chin Wang (Journal of Marine Science and Engineering, 2024)
Underwater images often encounter challenges such as attenuation, color distortion, and noise caused by artificial lighting sources. These imperfections not only degrade image quality but also impose constraints on related application tasks. Improving underwater image quality is crucial for underwater activities. However, obtaining clear underwater images has been a challenge, because scattering and blur hinder the rendering of true underwater colors, affecting the accuracy of underwater exploration. Therefore, this paper proposes a new deep network model for single underwater image enhancement. More specifically, our framework includes a light field module (LFM) and sketch module, aiming at the generation of a light field map of the target image for improving the color representation and preserving the details of the original image by providing contour information. The restored underwater image is gradually enhanced, guided by the light field map. The experimental results show the better image restoration effectiveness, both quantitatively and qualitatively, of the proposed method with a lower (or comparable) computing cost, compared with the state-of-the-art approaches.

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Backward and forward simulation of polycyclic aromatic hydrocarbons by the grid-scale model _validation and applications for environmental management - Ming-Tsuen Hsieh; Wen-Yu Chung; Shoiw-Mei Tseng; Pei-Chi Shih; Shau-Ku Huang; Chon-Lin Lee (Atmospheric Environment, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Dinaciclib inhibits the growth of acute myeloid leukemia cells through either cell cycle-related or ERK1/STAT3/MYC pathways - Chieh-Lin Jerry Teng; Pang-Ting Cheng; Yu-Chiao Cheng; Jia-Rung Tsai; Mei-Chih Chen; Ho Lin (Toxicology in Vitro, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Thermal regulation of photovoltaic panels using shape-stabilized phase change materials supported by exfoliated graphite/graphene nanofillers - Xinnian Guo; Kai Zheng; Hongqi Shi; Lin Chen; Yang Shen; Jiajia Chen; Xu Tao; Mei Yu (Journal of Cleaner Production, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Electropolymerization stabilized bipolar metal coordination complex for high-performance dual-ion batteries - Chen-xing Zhang; Xian-he Chen; Wei-sheng Zhang; Yue Wang; Shi-lin Mei; Yu-Wu Zhong; Chang-Jiang Yao (Chemical Engineering Journal, 2024)

Heteronemin promotes iron-dependent cell death in pancreatic cancer - Gizem Kaftan; Mümin Alper Erdoğan; Mohamed El-Shazly; Mei-Chin Lu; Shou-Ping Shih; Hung-Yu Lin; Luciano Saso; Güliz Armagan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Three chemosensory proteins enriched in antennae and tarsi of Rhaphuma horsfieldi differentially contribute to the binding of insecticides - Yu-Juan Yao; Ning-Na Yin; Lin-Mei Pu; An-Jing Yang; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2024)

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Chitosan composite films based on tea seed oil nano-microcapsules: Antibacterial, antioxidant and physicochemical properties - Qiuya Ji; Zhou Jin; Wanlu Ding; Yating Wu; Chunjie Liu; Kang Yu; Nannan Zhang; Guoguo Jin; Peiran Lu; Di Bao; Lin Mei (Food Packaging and Shelf Life, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Engineering a Pseudomonas putida as living quorum quencher for biofilm formation inhibition, benzenes degradation, and environmental risk evaluation - Yi-Mei Xue; Yong-Chao Wang; Yu-Ting Lin; Guan-Yu Jiang; Rui Chen; Ruo-Lin Qin; Xiao-Qiang Jia; Can Wang (Water Research, 2023)

An accurate and efficient HOS-meshfree CFD coupling method for simulating strong nonlinear wave–body interactions - Chun-Mei Xie; Jun-Cheng Yang; Peng-Nan Sun; Hong-Guan Lyu; Jun Yu; Yong-Lin Ye (Ocean Engineering, 2023)

Development of a sampling assembly for PM2.5 CEMS - Shibo Wang; Yu-Mei Kuo; Chih-Wei Lin; Sheng-Hsiu Huang; Chih-Chieh Chen (Journal of Aerosol Science, 2023)

Fabrication of diamond/copper composite thin plate based on a single-layer close packed diamond particles network for heat dissipation - Jia-wan Peng; Feng-lin Zhang; Yu-mei Zhou; Ling-kang Xiong; Yao-jie Huang; Hong-qun Tang (Chemical Engineering Journal, 2023)

Oxygen doped graphite carbon nitride as efficient metal-free catalyst for peroxymonosulfate activation: Performance, mechanism and theoretical calculation - Shaofeng Xiang; Yu Lin; Tongda Chang; Bingrui Mei; Yuhang Liang; Ziqian Wang; Wenwu Sun; Chun Cai (Chemosphere, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Polyphenolic glycosides with unusual four-membered ring possessing anti-Parkinson's disease potential from black wolfberry - Yi-Kao Hu; Xiao-Lin Bai; Guang-Yu Shi; Yong-Mei Zhang; Xun Liao (Phytochemistry, 2023)

Monitoring regional soil organic matter content using a spatiotemporal model with time-series synthetic Landsat images - Mei-Wei Zhang; Xiao-Qing Wang; Xiao-Gang Ding; Hua-Lei Yang; Qian Guo; Ling-Tao Zeng; Yu-Pei Cui; Xiao-Lin Sun (Geoderma Regional, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

β-Cyclodextrin network crosslinked by novel phosphonium-based tetrakiscarboxylic acid derived from PH3 tail gas: Synthesis and application for rapid removal of organic dyes from wastewater - Yu-Lin Hong; Jian Sun; Xiu-Qin Fang; Qing-Wen Liu; Chang Wang; Cheng-Mei Liu (Carbohydrate Polymers, 2023)

Detection of walnut oil adulterated with high-linoleic acid vegetable oils using triacylglycerol pseudotargeted method based on SFC-QTOF-MS - Jing-Jing Zhang; Yan Gao; Mei-Ling Zhao; Xiao Xu; Bo-Nan Xi; Li-Ke Lin; Jing-Yi Zheng; Bang Chen; Yu Shu; Cong Li; Yehua Shen (Food Chemistry, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Establishment of a lipopolysaccharide-induced inflammation model of human fetal colon cells - Keqi Yu; Shengtao Liao; Chuanfei Li; Ya Song; Zhechuan Mei; Lin Lv (Molecular Biology Reports, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

MiR-370-3p aggravates blood–brain barrier injury and neuron apoptosis by targeting SMURF1 to activate the TLR4/MyD88/NF-κB signaling in sepsis-associated encephalopathy - Neng Wang; Dan Zhong; Jie Lin; Mei Ye; Yu Chen; Lili Wang; Mei Chen; Cong Luo (Molecular & Cellular Toxicology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

P2X7Rs: new therapeutic targets for osteoporosis - Haoyun Huang; Yu-Mei He; Miao-Miao Lin; Yanchao Wang; Xiaomei Zhang; Li Liang; Xueling He (Purinergic Signalling, 2023)
Increasing evidence suggests that both the occurrence and progression of osteoporosis are associated with inflammation, especially in primary osteoporosis. The maintenance of skeletal homeostasis is dependent on the complex regulation of bone metabolism. Numerous evidence suggested that purinoceptor networks are essential for bone homeostasis. In this review, the relationship between inflammation and the development of osteoporosis and the role of P2X7 receptor (P2X7R) in regulating the dynamic regulation of bone reconstruction were covered. We also discussed how P2X7R regulates the balance between resorption and bone formation by osteoblasts and reviewed the relevance of P2X7R polymorphisms in skeletal physiology. Finally, we analyzed potential targets of P2X7R for osteoporosis.

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Mei-Jie Yang; Ying Shi; Zhi-Shu Lin; Pu Shi; Zhi Hu; Cong Zhou; Peng-Peng Hu; Zheng-Lin Yu; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa , but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa . This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa , which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.

A Novel Variable Weight VIKOR Grade Assessment Method for Waterway Navigation Safe Routes Selection - Gao-Feng Yu; Yu-Jin Lin; Xiao-Mei Luo (Journal of Marine Science and Engineering, 2023)
According to the characteristics of waterway navigation safe routes selection, and considering the individual feelings and group benefits of information, as well as no-compensation information between indexes, this paper describes the safe rating of waterway navigation routes, and then puts forward an evaluation model of and method for waterway navigation safe route selection based on variable weight VIKOR. First of all, from the concept and connotation of grade assessment, this paper describes the safe rating of waterway navigation routes, so as to avoid confusing the two essential different problems of safe rating and ranking. Then, the evaluation indexes and membership function of the appropriate grade of the safe rating of waterway navigation route are constructed, and the weights of an evaluation index based on entropy are proposed. Secondly, a variable weight VIKOR evaluation model and a binary semantic evaluation method for the safe grading of waterway navigation safe routes are proposed. Finally, through case study and comparative analysis, the rationality and feasibility of the model and method proposed in this paper are illustrated. This model can better reflect the connotation and characteristics of the appropriate grade assessment of waterway navigation safe routes, and provides new approaches and methods to support the development and management of waterway navigation safe route selection.

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

Associations between maternal phthalate exposure and neonatal neurobehaviors: The Taiwan maternal and infant cohort study (TMICS) - Hsing-Kang Chen; Shu-Li Wang; Yu-Hsun Chang; Chien-Wen Sun; Ming-Tsang Wu; Mei-Lien Chen; Yu-Jie Lin; Chia-Jung Hsieh (Environmental Pollution, 2023)

Source-specific health risk analysis on atmospheric hazardous volatile organic compounds (HVOCs) in Nanjing, East China - Yu-Chi Lin; Zi-Jin Zhang; Meng-Yao Cao; Mei-Yi Fan; Ahsan Mozaffar; Ming-Yuan Yu; Feng Xie; Yan-Lin Zhang (Atmospheric Environment, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Gastropod chemoreception behaviors—Mechanisms underlying the perception and location of targets and implications for shellfish fishery development in aquatic environments - Zheng-Lin Yu; Mei-Jie Yang; Hao Song; Tao Zhang; Xiu-Tang Yuan (Frontiers in Marine Science, 2023)
Chemoreception is one of the most important senses and it plays a key role in the survival and adaptation of animals to their environments. Many gastropods, such as Rapana venosa and Neptunea cumingii , have emerged as economically important shellfish. Meanwhile, invasive gastropods have destroyed commercial shellfisheries in many countries. Given the importance of chemoreception in the behavior of aquatic gastropods, the mechanism of their chemical perception has recently garnered attention. To provide a foundation for understanding the chemoreception of aquatic gastropods, we reviewed recent studies and summarized the chemoreception behaviors and mechanisms that gastropods use to perceive and locate targets in aquatic environments, along with relevant molecular and genetic insights. We highlight several of the implications of these studies for chemoreception-related research and shellfish fishery development. This review should aid in the rational development and utilization of gastropod resources as well as in controlling the populations of invasive species.

Transcriptomics and metabolomics together reveal the underlying mechanism of heroin hepatotoxicity - Yingbiao Yue; Lei Zou; Jie Tao; Lin Yin; Zhenrong Xie; Yu Xia; Zunyue Zhang; Kunhua Wang; Mei Zhu (Toxicology, 2023)

Seasonal variations of low molecular alkyl amines in PM2.5 in a North China Plain industrial city: Importance of secondary formation and combustion emissions - Xiao-Ying Yang; Fang Cao; Mei-Yi Fan; Yu-Chi Lin; Feng Xie; Yan-Lin Zhang (Science of The Total Environment, 2023)

Do sustainability committees reduce electricity use in Taiwan? Mitigating electricity regulation as motivation - Yu-Lin Chen; Mei-Chu Huang (Journal of Cleaner Production, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Correction to: Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy - Matthew M. Bower; Shuichi Suzuki; Kiarash Golshani; Li-Mei Lin; Mohammad Shafie; Hermelinda G. Abcede; Jay Shah; Dana Stradling; Wengui Yu (Translational Stroke Research, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy - Matthew M. Bower; Shuichi Suzuki; Kiarash Golshani; Li-Mei Lin; Mohammad Shafie; Hermelinda G. Abcede; Jay Shah; Dana Stradling; Wengui Yu (Translational Stroke Research, 2022)
Cerebral reperfusion injury is the major complication of mechanical thrombectomy (MT) for acute ischemic stroke (AIS). Contrast extravasation (CE) and intracranial hemorrhage (ICH) are the key radiographical features of cerebral reperfusion injury. The aim of this study was to investigate CE and ICH after MT in the anterior and posterior circulation, and their effect on functional outcome. This is a retrospective study of all consecutive patients who were treated with MT for AIS at University of California Irvine Medical Center between January 1, 2014, and December 31, 2017. Patient characteristics, clinical features, procedural variables, contrast extravasation, ICH, and outcomes after MT were analyzed. A total of 131 patients with anterior circulation (AC) stroke and 25 patients with posterior circulation (PC) stroke underwent MT during the study period. There was no statistically significant difference in admission NIHSS score, blood pressure, rate of receiving intravenous tPA, procedural variables, contrast extravasation, and symptomatic ICH between the 2 groups. Patients with PC stroke had a similar rate of favorable outcome (mRS 0–2) but significantly higher mortality (40.0% vs. 10.7%, p < 0.01) than patients with AC stroke. Multivariate regression analysis identified initial NIHSS score (OR 1.1, CI 1.0–1.2, p = 0.01), number of passes with stent retriever (OR 2.1, CI 1.3–3.6, p < 0.01), and PC stroke (OR 9.3, CI 2.5–35.1, p < 0.01) as independent risk factors for death. There was no significant difference in functional outcomes between patients with and without evidence of cerebral reperfusion injury after MT. We demonstrated that AC and PC stroke had similar rates of cerebral reperfusion injury and favorable outcome after MT. Cerebral reperfusion injury is not a significant independent risk factor for poor functional outcome.

Shoot organogenesis and somatic embryogenesis in leaf tissue of Pulsatilla tongkangensis Y.N. Lee & T.C. Lee - Xiao-mei Zhao; Yu-ji Lian; Ze-lin Jin; Xue-jie Zhang; Yan Y; Shou-jin Fan (Plant Biotechnology Reports, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Development of wheat-Dasypyrum villosum T6V#4S·6AL translocation lines with enhanced inheritance for powdery mildew resistance - Xiaolan Ma; Yanan Chang; Jingnan Chen; Mei Yu; Baicui Wang; Xingguo Ye; Zhishan Lin (Theoretical and Applied Genetics, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

The management of bone defect using long non-coding RNA as a potential biomarker for regulating the osteogenic differentiation process - Jia-lin Liu; Yan-shi Liu; Mei-jie Zheng; Hui-yu He (Molecular Biology Reports, 2022)
Tissue engineered bone brings hope to the treatment of bone defects, and the osteogenic differentiation of stem cells is the key link. Inducing osteogenic differentiation of stem cells may be a potential approach to promote bone regeneration. In recent years, lncRNA has been studied in the field increasingly, which is believed can regulate cell cycle, proliferation, metastasis, differentiation and immunity, participating in a variety of physiology and pathology processes. At present, it has been confirmed that certain lncRNAs regulate the osteogenesis of stem cells and take part in mediating signaling pathways including Wnt/β-catenin, MAPK, TGF-β/BMP, and Notch pathways. Here, we provided an overview of lncRNA, reviewed its researches in the osteogenic differentiation of stem cells, emphasized the importance of lncRNA in bone regeneration, and focused on the roles of lncRNA in signaling pathways, in order to make adequate preparations for applying lncRNA to bone tissue Engineering, letting it regulate the osteogenic differentiation of stem cells for bone regeneration.

Description of Aureibaculum luteum sp. nov. and Aureibaculum flavum sp. nov. isolated from Antarctic intertidal sediments - Xiao-yan He; Ning-hua Liu; Chao-yi Lin; Mei-ling Sun; Xiu-lan Chen; Yu-zhong Zhang; Yu-qiang Zhang; Xi-ying Zhang (Antonie van Leeuwenhoek, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Current Dependent Dispersal Characteristics of Japanese Glass Eel around Taiwan - Kuan-Mei Hsiung; Yen-Ting Lin; Yu-San Han (Journal of Marine Science and Engineering, 2022)
Japanese eel larvae are passively transported to the East Asian Continental Shelf by the North Equatorial Current, Kuroshio and Kuroshio intrusion currents, and coastal currents. Previous studies have investigated the dispersal characteristics and pathways of Japanese glass eels. However, there are still limitations in these studies. According to long-term (2010–2020) catch data from the Fisheries Agency in Taiwan, the distribution and time series of glass eels recruitment to Taiwan are closely related to the surrounding ocean currents. Recruitment begins in eastern Taiwan via the mainstream Kuroshio and in southern Taiwan via the Taiwan Strait Warm Current. In central Taiwan, recruitment occurs from southern Taiwan, as well as from mainland China via the southern branch of the China Coast Current (CCC). The latest recruitment occurred in northern Taiwan and mainly comprised glass eels from mainland China via the northern branch of the CCC. A stronger monsoon during the La Niña phase could affect the recruitment time series in northern and eastern Taiwan. This study suggests that the recruitment directionality of glass eels is an indicator of the flow field of ocean/coastal currents and elucidates the dispersal characteristics of glass eels in the waters around Taiwan.

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Multifunctional graphene-based nanocomposites for simultaneous enhanced photocatalytic degradation and photothermal antibacterial activity by visible light - Ya-kun Lv; Lin Mei; Liu-xue Zhang; De-hong Yang; Zi-yu Yin (Environmental Science and Pollution Research, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease - Hsu-Heng Yen; Ping-Yu Wu; Pei-Yuan Su; Chia-Wei Yang; Yang-Yuan Chen; Mei-Fen Chen; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2021)
Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients ( n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep learning model training, and 449 images were validated for the performance test. Two expert endoscopists classified the images into different classes based on their appearance. Four deep learning models, including Mobile Net V2, VGG16, Inception V4, and ResNet50, were proposed and pre-trained by ImageNet with the established convolutional neural network algorithm. A comparison of the endoscopists and trained deep learning model was performed to evaluate the model’s performance on a dataset of 449 testing images. Results The results first presented the performance comparisons of four deep learning models. The Mobile Net V2 presented the optimal performance of the proposal models. The Mobile Net V2 was chosen for further comparing the performance with the diagnostic results obtained by one senior and one novice endoscopists. The sensitivity and specificity were acceptable for the prediction of “normal” lesions in both 3-class and 4-class classifications. For the 3-class category, the sensitivity and specificity were 94.83% and 92.36%, respectively. For the 4-class category, the sensitivity and specificity were 95.40% and 92.70%, respectively. The interobserver agreement of the testing dataset of the model was moderate to substantial with the senior endoscopist. The accuracy of the determination of endoscopic therapy required and high-risk endoscopic therapy of the deep learning model was higher than that of the novice endoscopist. Conclusions In this study, the deep learning model performed better than inexperienced endoscopists. Further improvement of the model may aid in clinical decision-making during clinical practice, especially for trainee endoscopist.

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Assessing ecological health of mangrove ecosystems along South China Coast by the pressure–state–response (PSR) model - Yu-Tu Wang; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Ji-Dong Gu (Ecotoxicology, 2021)

Identification and characterization of CONSTANS-like genes from Curcuma alismatifolia - Yuan-Yuan Li; Xiao-Huang Chen; Hui-Wen Yu; Qi-Lin Tian; Luan-Mei Lu (Horticulture, Environment, and Biotechnology, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Adaptive Evolution of Chalcone Isomerase Superfamily in Fagaceae - Li-Mei Lin; Hong-Yu Guo; Xin Song; Duo-Duo Zhang; Yue-Hong Long; Zhao-Bin Xing (Biochemical Genetics, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata - I-Ting Weng; Yen-An Lin; Guan-Yu Chen; Hsiu-Mei Chiang; Yi-Jung Liu; Chao-Jung Chen; Yu-Hsuan Lan; Chia-Lin Lee (Natural Product Research, 2020)

Identification and validation of stable quantitative trait loci for grain filling rate in common wheat (Triticum aestivum L.) - Yu Lin; Xiaojun Jiang; Yang Tao; Xilan Yang; Zhiqiang Wang; Fangkun Wu; Shihang Liu; Caixia Li; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; et al. (Theoretical and Applied Genetics, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Population Structure of the World Vegetable Center Mungbean Mini Core Collection and Genome-Wide Association Mapping of Loci Associated with Variation of Seed Coat Luster - Caleb Manamik Breria; Ching Hsiang Hsieh; Jo-Yi Yen; Ramakrishnan Nair; Chen-Yu Lin; Shu-Mei Huang; Thomas J. Noble; Roland Schafleitner (Tropical Plant Biology, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Forecasts of MJO Events during DYNAMO with a Coupled Atmosphere-Ocean Model: Sensitivity to Cumulus Parameterization Scheme - Mei-Yu Chang; Tim Li; Pay-Liam Lin; Ting-Huai Chang (Journal of Meteorological Research, 2019)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Evaluation of Coherence Between ECG and PPG Derived Parameters on Heart Rate Variability and Respiration in Healthy Volunteers With/Without Controlled Breathing - Hao-Yu Jan; Mei-Fen Chen; Tieh-Cheng Fu; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Design, synthesis and biological evaluation of novel indone derivatives as selective ERβ modulators - Xi-Xi Liu; Mei-Lin Tang; Chen Zhong; Yun Tang; Jian-Ming Yu; Xun Sun (Medicinal Chemistry Research, 2019)

Quantitative trait locus mapping for panicle exsertion length in common wheat using two related recombinant inbred line populations - Yang Tao; Xin Yi; Yu Lin; Zhiqiang Wang; Fangkun Wu; Xiaojun Jiang; Shihang Liu; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; Youliang Zheng; et al. (Euphytica, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Risk factors and drug resistance in early-onset neonatal group B streptococcal disease - Ying-wei Wang; Yao-qiang Du; Xiao-lin Miao; Guang-yong Ye; Yi-yun Wang; Ai-bo Xu; Yun-zhong Jing; Yu Tong; Kai Xu; Mei-qin Zheng; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2018)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

A Novel MYCN Variant Associated with Intellectual Disability Regulates Neuronal Development - Xiuya Yu; Liyuan Hu; Xu Liu; Guodong Zhan; Mei Mei; Huijun Wang; Xiaohua Zhang; Zilong Qiu; Wenhao Zhou; Lin Yang (Neuroscience Bulletin, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

A New Approach of Rpf Addition to Explore Bacterial Consortium for Enhanced Phenol Degradation Under High Salinity Conditions - Ziqiao Li; Yunge Zhang; Yuyang Wang; Rongwu Mei; Yu Zhang; Muhammad Zaffar Hashmi; Hongjun Lin; Xiaomei Su (Current Microbiology, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

A new antiviral pregnane from a gorgonian-derived Cladosporium sp. fungus - Mei-Lin Yu; Fei-Fei Guan; Fei Cao; Yan-Lai Jia; Chang-Yun Wang (Natural Product Research, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Male-Produced Aggregation Pheromone of Coffee Bean Weevil, Araecerus fasciculatus - Shuai Yang; Xiao-Fang Zhang; Yu-Lin Gao; Dan Chen; Dong-Mei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Grape hexokinases are involved in the expression regulation of sucrose synthase- and cell wall invertase-encoding genes by glucose and ABA - Xiu-Qin Wang; Li-Li Zheng; Hao Lin; Fei Yu; Li-Hui Sun; Li-Mei Li (Plant Molecular Biology, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Migration of styrene and ethylbenzene from virgin and recycled expanded polystyrene containers and discrimination of these two kinds of polystyrene by principal component analysis - Qin-Bao Lin; Xue-Chao Song; Hong Fang; Yu-Mei Wu; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Design of wireless multi-parameter monitoring system for oral feeding of premature infants - Yu-Lin Wang; Hsing-Chien Kuo; Lin-Yu Wang; Mei-Ju Ko; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Resistance to viral yellow leaf curl in tomato through RNAi targeting two Begomovirus species strains - Huei-mei Chen; Chen-yu Lin; Wen-shi Tsai; Lawrence Kenyon; Ming-tsair Chan; Jo-yi Yen; Shao-yu Chang; Robert de la Peña; Roland Schafleitner (Journal of Plant Biochemistry and Biotechnology, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Distribution and sources of the polycyclic aromatic hydrocarbons in the sediments of the Pearl River estuary, China - Jian-Dong Zhang; You-Shao Wang; Hao Cheng; Zhao-Yu Jiang; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Variation of phytoplankton community structure from the Pearl River estuary to South China Sea - Zhao-Yu Jiang; You-Shao Wang; Hao Cheng; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Effect of antioxidants and light stabilisers on silver migration from nanosilver-polyethylene composite packaging films into food simulants - Qi-Zhi Su; Qin-Bao Lin; Chao-Fang Chen; Yu-Mei Wu; Li-Bing Wu; Xiao-Qing Chen; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2015)

Phylogenetic diversity on housekeeping and symbiotic genes of rhizobial from Sphaerophysa in China - Lin Xu; Osama Abdalla Mohamad; Yin Shan Ma; Yu Mei Zhang; Zhao Yu Kong (World Journal of Microbiology and Biotechnology, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Medullo-ponto-cerebellar white matter degeneration altered brain network organization and cortical morphology in multiple system atrophy - Chia-Feng Lu; Po-Shan Wang; Yuan-Lin Lao; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Brain Structure and Function, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Synthesis, characterization, and DNA binding of a novel ligand and its Cu(II) complex - Mei-Jin Li; Tao-Yu Lan; Zhi-Shan Lin; Changqing Yi; Guo-Nan Chen (JBIC Journal of Biological Inorganic Chemistry, 2013)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Distribution and temporal trend of polybrominated diphenyl ethers in one Shanghai municipal landfill, China - Kai Huang; Jie Guo; Kuang-fei Lin; Xiao-yu Zhou; Jun-xia Wang; Peng Zhou; Feng Xu; Mei-Lan Zhang (Environmental Science and Pollution Research, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Yi-sheng Chen; Hui-chung Wu; Chiung-mei Wang; Chia-chun Lin; Yi-ting Chen; Yu-jyun Jhong; Fujitoshi Yanagida (Folia Microbiologica, 2013)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Novel differential transcript expression identified by LongSAGE in the mouse endometrium during the implantation window - Yu-Bin Ding; Jun-Lin He; Xue-Mei Chen; Xue-Qing Liu; Ying-Xiong Wang (Molecular Biology Reports, 2013)

Haem Oxygenase-1 is Involved in Hydrogen Sulfide-induced Cucumber Adventitious Root Formation - Yu-Ting Lin; Mei-Yue Li; Wei-Ti Cui; Wei Lu; Wen-Biao Shen (Journal of Plant Growth Regulation, 2012)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Ralstonia solanacearum nlpD (RSc1206) contributes to host adaptation - Chi-Yin Hsieh; Jaw-Fen Wang; Pei-Cheng Huang; Der-Kang Lu; Yu-Mei Lin; Wen-Chieh Yang; Chiu-Ping Cheng (European Journal of Plant Pathology, 2012)

Protoplast isolation and culture for somatic hybridisation of rapid cycling Brassica rapa with ‘Anand’ CMS and Brassica juncea - Yu-Ji Lian; Xiao-Mei Zhao; Guang-Zhe Lin; Hak-tae Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Calcitonin gene-related peptide released from endothelial progenitor cells inhibits the proliferation of rat vascular smooth muscle cells induced by angiotensin II - Li Fang; Mei-Fang Chen; Zhi-Lin Xiao; Yin Liu; Guo-Long Yu; Xiao-Bin Chen; Xiu-Mei Xie (Molecular and Cellular Biochemistry, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Somatic embryogenesis and shoot organogenesis in the medicinal plant Pulsatilla koreana Nakai - Guang-Zhe Lin; Xiao-Mei Zhao; Soon-Kwan Hong; Yu-Ji Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Health risk of semi-volatile organic pollutants in Wujin river inflow into Taihu Lake - Rongfei Zhang; Weili Wang; Xiaorong Shi; Xiezhi Yu; Mei Li; Lin Xiao; Yibin Cui (Ecotoxicology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Phytoplankton variation and its relationship with the environment in Xiangxi Bay in spring after damming of the Three-Gorges, China - Guangjie Zhou; Xuemin Zhao; Yonghong Bi; Yubin Liang; Jianlin Hu; Min Yang; Yu Mei; Kongxian Zhu; Lin Zhang; Zhengyu Hu (Environmental Monitoring and Assessment, 2011)

Production and genetic characterization of somatic hybrids between leaf mustard (Brassica juncea) and broccoli (Brassica oleracea) - Yu-Ji Lian; Guang-Zhe Lin; Xiao-Mei Zhao; Hak-Tae Lim (In Vitro Cellular & Developmental Biology - Plant, 2011)

Characterization and expression of chicken selenoprotein W - Bor-Rung Ou; Mei-Jung Jiang; Chao-Hsiang Lin; Yu-Chuan Liang; Kuei-Jen Lee; Jan-Ying Yeh (BioMetals, 2011)

Gating-Related Molecular Motions in the Extracellular Domain of the IKs Channel: Implications for IKs Channelopathy - Yu Hong Wang; Min Jiang; Xu Lin Xu; Kai-Ling Hsu; Mei Zhang; Gea-Ny Tseng (The Journal of Membrane Biology, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Functional analysis of Spodoptera litura nucleopolyhedrovirus p49 gene during Autographa californica nucleopolyhedrovirus infection of SpLi-221 cells - Tiehao Lin; Mei Yu; Wenbi Wu; Qian Yu; Qingbei Weng; Kai Yang; Meijin Yuan; Yi Pang (Virus Genes, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Transferability of rice SSR markers to bamboo - Shu-Yun Chen; Yu-Tsung Lin; Chia-Wei Lin; Wei-Yu Chen; Chih Hung Yang; Hsin-Mei Ku (Euphytica, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

In-Silico Approaches to Multi-target Drug Discovery - Xiao Hua Ma; Zhe Shi; Chunyan Tan; Yuyang Jiang; Mei Lin Go; Boon Chuan Low; Yu Zong Chen (Pharmaceutical Research, 2010)

Intratumoral as well as peritumoral lymphatic vessel invasion correlates with lymph node metastasis and unfavourable outcome in colorectal cancer - Mei Lin; Shu-Pei Ma; Hui-Zhong Lin; Ping Ji; Dan Xie; Jian-Xian Yu (Clinical & Experimental Metastasis, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Enhanced flavonoid production in hairy root cultures of Glycyrrhiza uralensis Fisch by combining the over-expression of chalcone isomerase gene with the elicitation treatment - Hai-Chao Zhang; Jing-Mei Liu; Hong-Yu Lu; Shan-Lin Gao (Plant Cell Reports, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Effects of cannabinoid CB1 receptor antagonist rimonabant in consolidation and reconsolidation of methamphetamine reward memory in mice - Lu-lu Yu; Xue-yi Wang; Mei Zhao; Yu Liu; Yan-qin Li; Fang-qiong Li; Xiaoyi Wang; Yan-xue Xue; Lin Lu (Psychopharmacology, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

New norsesquiterpene and sesquiterpene from a soft coral of the genus Nephthea - Ruo-Lin Yang; Yun-Yan Kuang; Jing-Yu Su; Long-Mei Zeng (Natural Product Research, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Ri-mediated Transformation of Glycyrrhiza uralensis with a Squalene Synthase Gene (GuSQS1) for Production of Glycyrrhizin - Hong-Yu Lu; Jing-Mei Liu; Hai-Chao Zhang; Tao Yin; Shan-Lin Gao (Plant Molecular Biology Reporter, 2008)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

Evolutionary characterization of influenza virus A/duck/Hubei/W1/2004 (H9N2) isolated from central China - Xiao-Juan Xu; Gao-Yuan Xu; Hong-Bo Zhou; Zheng-Jun Yu; An-Ding Zhang; Yun-Feng Song; Mei-Lin Jin; Huan-Chun Chen (Virus Genes, 2008)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

Identification of the Apoptosis Inhibitor Gene p49 of Spodoptera litura Multicapsid Nucleopolyhedrovirus - Mei Yu; Zhaofei Li; Kai Yang; Tiehao Lin; Yingxue Gong; Lijing Pan; Yi Pang (Virus Genes, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

A Thermodynamic Interpretation of the Monod Equation - Yu Liu; Yue-Mei Lin; Shu-Fang Yang (Current Microbiology, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)